PENGARUH DRILL TRAINING TERHADAP KETEPATAN SMASH PESERTA EKSTRAKURIKULER BULUTANGKIS SMKN 5 PONTIANAK - Aditya Yoga Frastianto; Andika Triansyah; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem in this research is the low accuracy of extracurricular badminton smash at SMKN 5 Pontianak. The purpose of this study is to determine whether the drill training method had an effect on the smash accuracy of the badminton extracurricular participants at SMKN 5 Pontianak. The research method used in this research is experimental. The form of experimental design is by using the One Group Pretetst-posttest. The Sampling use total sampling, they are students of SMKN 5 Pontianak who took the badminton extracurricular amounted to 15 students. The data analysis was performed by t-test analysis. The results of the research and data analysis obtained tcount> ttable (8.29> 2.11479), which means that the hypothesis is accepted, there is an effect of drill training on the smash accuracy of badminton extracurricular participants at SMKN 5 Pontianak. By an increase percentage of 10.9%, this shows that there is an effect of smash accuracy of badminton extracurricular students at SMKN 5 Pontianak by using the drill training method.Keywords: Badminton Smash Accuracy, Drill Training